2019
DOI: 10.32098/mltj.03.2019.14
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between cardiovascular disease risk factors and Achilles tendon structural and mechanical properties in people with Type 2 Diabetes

Abstract: Background. Patients with diabetes have 44% greater risk of tendon rupture requiring hospitalisation. Despite this, in vivo research of the associations of diabetes and other cardiovascular disease risk factors on structural and mechanical properties of the Achilles tendon are sparsely studied. Methods. Inactive individuals with type 2 diabetes (n=33) underwent ultrasound and shear wave elastography imaging of their Achilles tendons bilaterally to measure thickness and shear wave velocity (SWV), an index of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In a study observing the micro-structure and morphology of the Achilles tendons of patients with long-term DM using an electron microscope, it was reported that such tendons have reduced fiber diameter, increased collagen fiber bulk density, and abnormal fiber morphology (4). These findings themselves suggest possible mechanisms underlying the findings of other reports indicating that (a) the hyperechoic appearance of diabetic muscles in ultrasound imaging correctly predicted diabetes in 70 of 79 patients (5); (b) long-term diabetes is associated with a high prevalence of chronic Achilles tendinopathy, including hypoechogenicity, entheseal thickening, and enthesophytes (2,6); and (c) diabetic tendons demonstrate inferior elasticity (Young modulus), maximum load, and stiffness levels (7,8). Theoretically, these respective muscle morphological and tendon microstructural changes are the causes of diabetic muscle force compromise, in addition to being evidence of diabetic complications in tissues with low reparative capacity.…”
Section: Introductionmentioning
confidence: 52%
“…In a study observing the micro-structure and morphology of the Achilles tendons of patients with long-term DM using an electron microscope, it was reported that such tendons have reduced fiber diameter, increased collagen fiber bulk density, and abnormal fiber morphology (4). These findings themselves suggest possible mechanisms underlying the findings of other reports indicating that (a) the hyperechoic appearance of diabetic muscles in ultrasound imaging correctly predicted diabetes in 70 of 79 patients (5); (b) long-term diabetes is associated with a high prevalence of chronic Achilles tendinopathy, including hypoechogenicity, entheseal thickening, and enthesophytes (2,6); and (c) diabetic tendons demonstrate inferior elasticity (Young modulus), maximum load, and stiffness levels (7,8). Theoretically, these respective muscle morphological and tendon microstructural changes are the causes of diabetic muscle force compromise, in addition to being evidence of diabetic complications in tissues with low reparative capacity.…”
Section: Introductionmentioning
confidence: 52%
“…Insulin combined with moderate-intensity exercise on a treadmill increased the physical fitness of DM1 animals, whereas sedentary animals exhibited decreased physical fitness regardless of IST use. Physical inactivity combined with a hyperglycemic state potentiates the chronic compli- cations of musculoskeletal (5,31) and cardiovascular (4,32) systems, which in turn can be mitigated by physical exercise (33,34). Together, that evidence reinforces the clinical benefits of physical exercise for diabetes.…”
Section: Discussionmentioning
confidence: 71%
“…Hypercholesterolemia was the most common metabolic condition in our study population of patients with ATRs. Serum cholesterol is carried in various form, of which LDL cholesterol (LDL-C) is the most atherogenic [25]. Indeed, patients with high levels of total cholesterol (>200 mg/dL; 5.17 mmol) and LDL cholesterol (>100 mg/dL; 2.58 mmol) can be diagnosed with hypercholesterolemia [26].…”
Section: Discussionmentioning
confidence: 99%